The effect of the YouTube subscriptions button in the real-world and cyberspace - Putra Aditya Lapalelo (Indonesian Journal of Social Sciences, 2021)
The virtual subscribe button feature on the YouTube platform, which is only the smallest technological element in cyberspace, has turned into a technology capable of dominating interactions in cyberspace and the real world. This growing influence cannot be separated from the subscribe button's function, which is increasingly changing, not just running a function to subscribe to the YouTube channel. Technically, this key determinism has turned into something very social to become a means of moving community groups to influence the economy, politics, social and culture. That can be seen from the results of observations of eight informants who are YouTube users. The eight informants acknowledged the subscribe button's existence, which has influenced social and economic interactions on social media in the last decade. Although several informants also pointed out that humans' role is still visible in the development of the subscriber button as one of the most crucial features in social media, YouTube, and the internet as a whole.